Processamento de aco inoxidavel superduplex uns s32520 por moagem de alta energia - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2008)
The proposal of the present work is the processing of UNS S32520 commercial duplex stainless steel by high energy milling. First, using hardness by microindentation, optical and scanning electron microgaphies tests, was studied the influence of annealing between 400ºC and 1000ºC, with aim in α’- phase and σ-phase precipitation. For it, was taken some samples from commercial stainless steel sheet and comparing with and without annealing condition. Moreover, turning chips were machined from the sheet and then embbrietled isothermically at 475 ºC, for α’-phase precipitation and at 800 ºC, for σ-phase precipitation. Later, these turning chips were processing in Spex and Attritor types of high energy milling. Some powders were achieved which were conformed in green compacts by cold pressure. The green compacts were sintered at 1200ºC for several times. The characterizations by optical and scanning electron microscopy showed grains microstructure with morphologies less oriented than as-received material, where were influenced by type of milling machine and time of sintering.
The UNS S32520 superduplex stainless steel processing by mechanical alloying
Keywords: aco inoxidavel superduplex; ferrita; austenita; moagem de alta energia; CNPQ::ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA